VEGFD protects retinal ganglion cells and, consequently, capillaries against excitotoxic injury - Schlüter, Annabelle; Aksan, Bahar; Diem, Ricarda; Fairless, Richard; Mauceri, Daniela (Molecular therapy. Methods & clinical development, 2020)
In the central nervous system, neurons and the vasculature influence each other. While it is well described that a functional vascular system is trophic to neurons and that vascular damage contributes to neurodegeneration, the opposite scenario in which neural damage might impact the microvasculature is less defined. In this study, using an in vivo excitotoxic approach in adult mice as a tool to cause specific damage to retinal ganglion cells, we detected subsequent damage to endothelial cells in retinal capillaries. Furthermore, we detected decreased expression of vascular endothelial growth factor D (VEGFD) in retinal ganglion cells. In vivo VEGFD supplementation via neuronal-specific viral-mediated expression or acute intravitreal delivery of the mature protein preserved the structural and functional integrity of retinal ganglion cells against excitotoxicity and, additionally, spared endothelial cells from degeneration. Viral-mediated suppression of expression of the VEGFD-binding receptor VEGFR3 in retinal ganglion cells revealed that VEGFD exerts its protective capacity directly on retinal ganglion cells, while protection of endothelial cells is the result of upheld neuronal integrity. These findings suggest that VEGFD supplementation might be a novel, clinically applicable approach for neuronal and vascular protection.
Available online 25 December 2019
Gesehen am 24.06.2020